What is the Impact of Brand Co-branding on Consumers’ Purchase Intention? - Cui, Jiani (Transactions on Economics, Business and Management Research, 2024)
Aiming at the difference in consumers’ purchases intention when different brands are co-branded with Luckin Coffee , we analyse the influence of co-branded products on consumers’ purchase intention through theoretical frameworks and empirical data , respectively . The results of correlation and pairwise analyses show that consumers have different judgements on the purchase intention of different sub-brands co-branded with the same main brand: the scarcity of the co-brand and brand equity affect consumers’ purchase intention. This implies that brands should make adjustments to the relevant factors when co-branding .